Avoiding “musty mutton chops”: the network narrative of an American merchant in London, 1771-1774 - Haggerty, John; Haggerty, Sheryllynne (Economic and Business History Society, 2018)
Historians have increasingly been using network and narrative analysis as a means by which to explore their data. By doing so, they are able to explore how actors of interest used their relationships to undertake business and economic endeavors, and how, in turn, these were shaped by the discourse to which they had access. This paper presents a novel methodology using visual analytics to combine both social network (relationship) and textual (sentiment) analysis to visualize the information contained in historical sources over time. The definition of network narrative posited in this paper allows the historian to quantify and therefore assess the impact of, and reaction to, endogenous and exogenous events on actor networks. In order demonstrate the applicability of this approach, we apply it to the case study of Joshua Johnson, an American merchant in London during the 1772 credit crisis. This paper builds on the more recent network studies which show that networks were not only complex, but changed over time in reaction to events.